Role of [18F] Fluoro-2-Deoxy-D-Glucose Positron Emission Tomography/Computed Tomography in the Diagnosis of Tonsillar Carcinoma in a Patient with Multiple Primary Carcinomas - Fernando, Patrick Earl Amparado; Ongkeko, Eduardo Erasto Santiago (World Journal of Nuclear Medicine, 2019)
Tonsillar carcinoma is not easily diagnosed on [18F] fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) scan; normal, inflamed, and infected tonsils also exhibit increased tracer uptake. We present a case of a 68-year-old male with colon and prostate carcinomas who was referred for a PET/CT scan. He presented with right cervical lymphadenopathy which, on fine-needle biopsy, was found to have atypical cells suspicious for malignancy. On PET/CT, the right cervical lymph nodes appeared hypermetabolic; subsequent excision biopsy revealed metastatic poorly differentiated carcinoma. Increased metabolic activity was also seen in the tonsils, the right more than the left, which was initially ascribed to be inflammatory or physiologic. On magnetic resonance imaging follow-up, however, a more prominent and more enhancing right palatine tonsil was observed, which on histopathology was consistent with squamous cell carcinoma. Determining the maximum standard uptake value ratio between the two tonsils could have been helpful in differentiating squamous cell tonsillar carcinoma from benign asymmetric FDG uptake in this case. On a background of enlarged cervical lymph nodes and known primary carcinomas, uptake in the tonsils should be thoroughly assessed before interpreting it as an inflammatory or physiologic variant, especially if there is asymmetry in FDG uptake.
Keywords: [18F] fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography scan; maximum standardized uptake value ratio; tonsillar carcinoma